Differential epigenetic regulation within an Arabidopsis retroposon family - Rangwala, S.H; Richards, E.J (Genetics (Austin), 2007)
We previously reported a novel family of Arabidopsis thaliana nonautonomous retroposons, Sadhu, showing epigenetic variation in natural populations. Here, we show that transcripts corresponding to Sadhu elements accumulate in a subset of mutants carrying disruptions in genes encoding chromatin modification enzymes, but are not significantly expressed in mutants defective in RNA silencing pathways, indicating that RNA-directed processes are not necessary to maintain transcriptional suppression of this class of retroelements. We focused our analysis on three representative elements showing differential responses to ddm1, met1, and hda6 mutations. These mutations had differing effects on cytosine methylation depending on the element and the sequence context. Curiously, the Sadhu6-1 element with the strongest CpHpG methylation is expressed in a met1 CpG methyltransferase mutant, but is not expressed in ddm1 or cmt3 mutants. Regardless of the mutant background, H3meK9 was found at silenced loci, while H3meK4 was restricted to expressed alleles. We discuss the different modes of regulation within this family and the potential impact of this regulation on the stability of silencing in natural populations.